"Is more, less?" : insect-insect interactions in a biological control context using water hyacinth as a model - Weyl, Philip Sebastian Richard (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2012)
Interactions between insects have been shown to be important regulators of population abundances and dynamics as well as drivers of spatial segregation and distribution. These are important aspects of the ecology of insects used in biological control and may have implications for the overall success of a particular programme. In the history of biological control there has been a tendency to release a suite of agents against a weed, which in some cases has increased the level of success, while in others little change has been observed. In most of these cases the implications of increasing the level of complexity of the system is not taken into account and there is little research on the effect of releasing another agent into the system. A brief meta-analysis was done on all the biological control programmes initiated in South Africa. Emphasis was placed on multi-species releases and the effects that overlapping niches were having on the number of agents responsible for the success of a programme. Where overlapping niches were present among agents released the number of agents responsible for success was lower than the number established. Water hyacinth, Eichhornia crassipes (Martius) Solms-Laubach in South Africa has more arthropod agents released against it than anywhere else in the world, yet control has been variable. If the biology and host utilisation of all the agents against water hyacinth is considered, a definite overlap of niches is apparent in at least one life stage of all the agents. Therefore the probability of these insects interacting is high, especially if they are established at the same site in the field. Three of the insects released in South Africa have been selected to investigate possible interactions. They are Neochetina eichhorniae Warner, Neochetina bruchi Hustache and Eccritotarsus catarinensis (Carvalho). Y-tube olfactometer bioassays were used to measure responses of these insects to water hyacinth with prior feeding damage by either conspecifics or heterospecifics. This was done to determine whether olfactory cues played a role in host acceptability and avoidance of conspecifics or heterospecifics. The insects were given a choice between damaged and undamaged plants in various combinations. There was a significant preference for the undamaged plants when given a choice between undamaged and damaged plants. However when the insects were given a choice between two damaged plants there was no discrimination between heterospecific or conspecific damaged plants. This may indicate that there is little or no ecological cost for the insect to share a plant with other insects utilising a similar resource. Insect "“ insect interactions were investigated in a common garden plot experiment to measure the impact that pairwise combinations of the insect may have on their performance. There was a significant interaction between the mirid E. catarinensis and the weevil N. eichhorniae, with the weevil not performing as well when in combination with the mirid than when alone. Interestingly there was a negative interaction between the two weevil species when in combination, however it was impossible to determine which species was being affected if not both. None of the insects performed significantly better when in combination with another insect. A field study on Wriggleswade Dam in the Eastern Cape, South Africa was initiated to determine whether the relationship between the mirid E. catarinensis and the weevil N. eichhorniae could be determined in the field. The performance of the insects at the different sites in the field suggests that there was an interaction between the agents. This interaction did not limit the establishment of either insect at a site, but it did result in one insect dominating at a site over another. Interactions between the three species of insect tested in this thesis suggest that there are both negative and neutral relationships between them. A basic comparison between the insect performances from 15 sites around the country was done to determine if the spatial segregation observed in the field could be extrapolated to the natural South African situation. The interaction observed between N. eichhorniae and E. catarinensis does seem to extrapolate to the general South African situation where there is definite spatial segregation on a landscape level. The co"“occurrence of the two Neochetina weevils at these sites suggests that the negative relationship observed between them in the common garden experiment does not extrapolate to the field. The results from this thesis suggest that the interactions between the agents tested would not limit establishment or have significant ramifications on performance. However, there may be spatial and temporal segregation of these species in the introduced range.
Keywords: Water hyacinth -- South Africa -- Eastern Cape; Water hyacinth -- Biological control -- South Africa -- Eastern Cape; Insects as biological pest control agents; Miridae -- South Africa -- Eastern Cape; Beetles -- South Africa -- Eastern Cape; Competition (Biology)